Research on the Impact of Ecological Civilization Construction on Environmental Pollution Control in China—Based on Differential Game Theory - Liuwei Zhao; Shuai Jin (Discrete Dynamics in Nature and Society)
With environmental pollution problems becoming more and more serious, administrators need to change their original system of performance achievement evaluation and build a new performance achievement view of ecological civilization. Based on the view of achievement evaluation of ecological civilization, this research develops a continuous-time differential game of environmental pollution control between local government and enterprises by taking into consideration dynamic change in pollutants in the environment into account. By analyzing the equilibrium solution of the game, the role of the assessment mechanism of ecological civilization is explored, and countermeasures are proposed to provide a scientific basis for improving the assessment mechanism of ecological civilization in China’s environmental pollution control. The results have shown that enterprises’ equilibrium pollutants output is negatively correlated to Ecological Civilization Index. Instead, the government’s efforts to curb pollutions are positively correlated to the environmental review. With th`at, lowering enterprises’ cost of production and pollution reduction alongside imposing more severe punishment would help improve pollution management. Setting up reasonable reward-punishment system would improve local governments’ pollution management. Elsewhere, the research employs the method of numerical simulation to testify the relationship among the importance of environmental review, enterprises’ pollutant output, and government’s efforts to manage pollutions. Finally, the research also suggests necessary measures to solve environmental pollutions and introduces a numerical simulation analysis.